2013
DOI: 10.1007/s13668-013-0068-9
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Adiposity and Breast Cancer Recurrence and Survival: A Review of the Recent Literature

Abstract: Breast Cancer (BC) is the most common and second deadliest malignancy among American women. Many factors contribute to BC prognosis but a key modifiable lifestyle factor is body weight. In this review, we update the reader on the association between adiposity and poor BC outcomes. We summarize the findings from studies that show obesity to be a risk factor for BC recurrence and reduced survival, including research that shows that treatment with aromatase inhibitors in hormone-receptor positive BC survivors who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 34 publications
1
81
0
4
Order By: Relevance
“…Obesity is associated with increased risk of breast cancer recurrence and mortality in both pre and postmenopausal women (83,84). Multiple studies have demonstrated that this association may be stronger in women with hormone receptor-positive tumors (85)(86)(87).…”
Section: Cancermentioning
confidence: 99%
“…Obesity is associated with increased risk of breast cancer recurrence and mortality in both pre and postmenopausal women (83,84). Multiple studies have demonstrated that this association may be stronger in women with hormone receptor-positive tumors (85)(86)(87).…”
Section: Cancermentioning
confidence: 99%
“…Others describe reductions in the energy expended, basal metabolic rate, and physical activity 9,10 . Another important factor is the combination of glucocorticoids and antiemetics used to minimize the side effects of CTx agents 8,11 . Psychological stress-related emotional volatility and start of menopause may also be related to weight gain during CTx 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is associated with locally advanced disease at diagnosis and, consequently, a poorer prognosis 11,16,19 . The mechanism has not been well-established, but high BMI values have been usually associated with greater concentrations of circulating sex hormones, insulin, and insulin growth factor, leading to a disequilibrium in the relationship between cell differentiation and apoptosis with a consequent progression and proliferation of tumor cells [16][17][18]20 .…”
Section: Introductionmentioning
confidence: 99%
“…These are important findings as higher levels of fat mass and lower levels of muscle mass have been related to poorer survival [41,42] and high risk of metabolic diseases [42][43][44] indicating the need to restore body composition of breast cancer survivors after treatments. Previous reviews have indicated that it is insufficient evidence for the effect of exercise on body composition in cancer patients [14,45], but the few studies addressing this topic have found similar results to ours, suggesting that exercise may be an efficient tool to restore energy balance and thus improve body composition [43,46].…”
Section: Discussionmentioning
confidence: 99%